The contribution of Regional Centers of Expertise for the implementation of the 2030 Agenda for Sustainable Development - Kalterina Shulla; Walter Leal Filho; Salim Lardjane; Jan Henning Sommer; Amanda Lange Salvia; Christian Borgemeister (Journal of Cleaner Production, 2019)
The implementation of the 2030 Agenda for Sustainable Development and the achievement of the 17 Sustainable Development Goals requires a fully integrated approach between sectors, disciplines, countries, and actors. On the fourth year of its implementation, the uptake of SDGs from non-state actors is increasing around the world, by developing engaging mechanisms for involvement at horizontal and vertical level. Considering that activation of existing partnerships is important for SDGs, in conjunction with creating new ones, this research has analysed the approach of global network of Regional Centers of Expertise on Education for Sustainable Development. An overview of involvement is done based on a survey data, by exploring collaboration in local, national and international scale. Through Hierarchical Classification Analysis, the networks are grouped into clusters with similar characteristics and discussions include challenges and potentialities for intensifying the contribution towards the 2030 Agenda.
Keywords: Sustainable Development Goals; Networks; Partnerships; Education